Investigation of Antioxidant Properties of Spearmint (Mentha spicata L.) - Elmastas, Mahfuz; Gncin, Ilhami; Qzturk, Lokman; Gokce, Isa (Asian Journal of Chemistry, 2016)
The antioxidant properties of ethanol extract of spearmint (Mentha spicata L.) (MS) were studied and evaluated using different antioxidant tests, including reducing power, free radical scavenging, superoxide anion radical scavenging and metal chelating activities. The concentration of 100 and 250 µg/mL of ethanol extract of spearmint (MS) showed 97 and 99 % inhibition on peroxidation of linoleic acid emulsion, respectively. On the other hand, 100 and 250 µg/mL of standard antioxidant such as BHA, BHT and a-tocopherol exhibited 85, 87 % (BHA), 97, 99 % (BHT) and 51, 77% (a-tocopherol) inhibition on peroxidation of linoleic acid emulsion, respectively. The ethanol extract of MS had effective reducing power, free radical scavenging and metal chelating activities at same concentration (50, 100 and 250 µg/mL). These various antioxidant activities were compared to standard antioxidants such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and a-tocopherol. In addition, total phenolic compounds in the ethanol extract were also determined as gallic acid equivalent.